2003
DOI: 10.1253/circj.67.431
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and 1-Year Prognosis of Medically Treated Patients With Chronic Heart Failure in Japan-Chronic Heart Failure Analysis Registry in Tohoku District (CHART)-

Abstract: The study was designed to characterize patients with chronic heart failure (CHF) in Japan in terms of the etiologies and prognosis. CHF was defined by ejection fraction (EF >or=50%), left ventricular diastolic dimension (LVDD >or=55 mm) or a past history of congestive heart failure. Among the 721 recruited patients, the most frequent etiology for CHF was dilated cardiomyopathy (DCM) in patients aged less than 59 years, and valvular heart disease (VHD) in those aged 70 years or more. The 1-year crude mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 23 publications
1
28
0
2
Order By: Relevance
“…8) Some investigations in Japanese subjects have shown that plasma BNP is useful as an independent factor for estimation of the outcome and prediction of sudden death. 9,10) On the other hand, plasma BNP has been reported to increase with increases in the grade of severity of heart disease according to the NYHA classification in a way similar to the plasma levels of ANP, cGMP, and norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…8) Some investigations in Japanese subjects have shown that plasma BNP is useful as an independent factor for estimation of the outcome and prediction of sudden death. 9,10) On the other hand, plasma BNP has been reported to increase with increases in the grade of severity of heart disease according to the NYHA classification in a way similar to the plasma levels of ANP, cGMP, and norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…The main protocol characteristics and results of some studies (87)(88)(89)(90)(91) that evaluated the prognostic value of CNH assays in patients with HF are reported in Table 6. In all of these studies, BNP and NT-proBNP (but not ANP and NT-proANP) were always found to be independent risk markers for morbidity and/or mortality (87)(88)(89).…”
Section: Prognosis In Hfmentioning
confidence: 99%
“…BNP is a strong predictor of morbidity and mortality in heart failure (51). It has been shown that BNP as well as troponin I and CK-MB levels were elevated in stress CMP as in heart failure or acute myocardial infarction, and increased BNP levels were related to clinical severity, hemodynamic stress, and myocardial contractility (37,38).…”
Section: G6mentioning
confidence: 99%